2011
DOI: 10.2753/ree1540-496x4703s204
|View full text |Cite
|
Sign up to set email alerts
|

Sovereign Risk Ratings: Biased Toward Developed Countries?

Abstract: Sovereign credit ratings are widely used measurements for "country risk" in international capital markets. However, they have been exposed to increasing criticism in the aftermath of the recent global financial crises. Many international authorities proposed new frameworks for the regulation and supervision of the credit rating sector, in which many countries have taken various steps in this respect. Yet the reliability of sovereign credit ratings has not been criticized in the literature. Using random effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 10 publications
2
35
0
Order By: Relevance
“…Among the earlier studies, Cosset and Roy (1991) and Cantor and Packer (1996) investigate the determinants of sovereign credit ratings by employing ordinary least squares (OLS). Frank and Cline (1971), Grinols (1976), Sergen (1977), and Saini and Bates (1978) employ discriminant analysis, whereas, Alexe et al (2003), Afonso (2003), Bissoondoya-Bheenick (2005), Bennell et al (2006), Afonso et al (2009), Gültekin-Karakaş et al (2011, and Erdem and Varli (2014) are the new generation studies that use ordered response models. Even though the results and findings of these studies vary, the predictive power of statistical models is very similar and relatively low.…”
Section: Sovereign Credit Ratingsmentioning
confidence: 96%
See 2 more Smart Citations
“…Among the earlier studies, Cosset and Roy (1991) and Cantor and Packer (1996) investigate the determinants of sovereign credit ratings by employing ordinary least squares (OLS). Frank and Cline (1971), Grinols (1976), Sergen (1977), and Saini and Bates (1978) employ discriminant analysis, whereas, Alexe et al (2003), Afonso (2003), Bissoondoya-Bheenick (2005), Bennell et al (2006), Afonso et al (2009), Gültekin-Karakaş et al (2011, and Erdem and Varli (2014) are the new generation studies that use ordered response models. Even though the results and findings of these studies vary, the predictive power of statistical models is very similar and relatively low.…”
Section: Sovereign Credit Ratingsmentioning
confidence: 96%
“…Despite they are easy to read, allow cross country comparisons, and therefore widely used by the parties participating in the global financial markets; sovereign credit ratings need serious reforms because their estimation methodology, accuracy and credibility of ratings are heavily debated in the recent crisis (Gültekin-Karakaş et al 2011). The debate is so intense, since sovereign credit ratings are not merely the risk measurements for countries but also for corporations.…”
Section: Sovereign Credit Ratingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gültekin-Karakaş et al, (2011) provide evidence that credit rating agencies give higher ratings to developed industrial countries than to emerging market economies regardless of macroeconomic fundamentals. Particularly puzzling is a higher credit rating of Western European countries in contrast to East European transition economies that ignores fiscal and current account balance positions.…”
Section: Domestic and International Factors Affecting Sovereign mentioning
confidence: 99%
“…The relationship between ratings and their determinants has been widely examined following the innovative studies of Cantor and Packer (1995) and Cantor and Packer (1996). Among many others, Afonso and Gomes (2011), Erdem and Varli (2014), Gültekin-Karaka¸s et al (2011) studied the determinants of ratings and found that the impact of fiscal balance on rating assessments is significant. All these authors conclude that CRAs attach considerable importance to fiscal balance meaning that the deterioration in fiscal balance is likely to trigger rating downgrades.…”
Section: Political Opportunism and Rating Changesmentioning
confidence: 99%